Management and Policy of Gestational Hypertension at the Sentru Formosa Clinic, Dili – Timor Leste - Suzete Bento Alves Pereira, Dilma (STIKES Hesti Wira Sriwijaya, 2026)
Introduction: Gestational hypertension is a leading cause of maternal and fetal morbidity and mortality, particularly in developing countries like Timor-Leste. As a primary healthcare facility, the Sentru Formosa Clinic still faces various challenges in managing gestational hypertension. This study aim was to Analyze the management and policies for handling gestational hypertension at the Sentru Formosa Clinic and formulate recommendations for improvement based on evidence-based policies and practices. Method: This study uses a qualitative descriptive approach through a literature review of WHO guidelines, ISSHP, and Timor Leste National Treatment Standards, as well as an analysis of the situation of antenatal care (ANC) services at the Sentru Formosa Clinic including the availability of facilities, clinical practices, and referral systems. Results: Several key issues were identified, including limited screening tools, the lack of standardized standard operating procedures (SOPs), low healthcare worker capacity in handling severe cases, a suboptimal referral system, and a lack of education for pregnant women. These conditions have the potential to lead to delays in the detection and treatment of gestational hypertension. Conclusion: Standardized operational policies are needed to improve the quality of screening, initial treatment, and referral systems for gestational hypertension. Implementing standard operating procedures (SOPs), increasing the capacity of healthcare workers, and strengthening the referral system are expected to reduce the risk of maternal and neonatal complications.